2015
DOI: 10.4172/2167-0277.1000192
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Obstructive Sleep Apnea Syndrome is related to Red Cell Distribution Width and Hematocrit Values

Abstract: Background: Obstructive sleep apnea syndrome (OSAS) is a common sleep disorder characterized by recurrent upper airway collapse during sleep. Recently, some hematological parameters as red cell distribution width (RDW), mean platelet volume (MPV), and platelet distribution width (PDW) have been emerged as inflammatory biomarkers. Limited, controversial data is available on the association between these hematological parameters and the severity of OSAS. Therefore, we aimed to investigate the levels of these par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…Regarding the comparison between OSA patients and controls in polysomnography and neck ultrasonography data, our results were consistent with Bidarian-Moniri et al [21], who found altered AHI depending on the position and were in accordance with Yousef and Alkhiary [22] who reported significantly higher oxygen desaturation index and significantly lower minimal oxygen saturation in OSA patients than controls. As expected, AHI demonstrated significantly higher values in OSA patients than controls in this study (mean ± SD = 32.05 ± 22.79; vs mean ± SD = 1.63 ± 1.64; P < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the comparison between OSA patients and controls in polysomnography and neck ultrasonography data, our results were consistent with Bidarian-Moniri et al [21], who found altered AHI depending on the position and were in accordance with Yousef and Alkhiary [22] who reported significantly higher oxygen desaturation index and significantly lower minimal oxygen saturation in OSA patients than controls. As expected, AHI demonstrated significantly higher values in OSA patients than controls in this study (mean ± SD = 32.05 ± 22.79; vs mean ± SD = 1.63 ± 1.64; P < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…RDW has been previously correlated with CRP and ESR values [ 15 ] and has been nominated as an index for estimating autoimmune disease activity [ 16 ] and a marker of subclinical inflammation, underlying atherosclerosis [ 15 ] and cardiovascular morbi-mortality [ 17 ]. OSA-induced repetitive hypoxia promotes accelerated erythropoiesis [ 43 ] which could explain a higher RDW in OSA [ 15 , 17 , 18 , 43 , 56 ]. Durmaz et al [ 57 ] have previously shown that RDW is a predictor of OSA burden in severe OSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Durmaz et al [ 57 ] have previously shown that RDW is a predictor of OSA burden in severe OSA patients. RDW values were previously correlated with AHI, DI, minimal nocturnal O2Sa and ESS results [ 18 , 58 , 59 , 60 , 61 ], suggesting that RDW could be used as an OSA screening tool in the general population. However, CPAP therapy seems to have little impact on RDW values [ 17 , 43 , 44 ]: while Leon Subias et al reported no changes in RDW after 1 year of CPAP [ 17 ], two other studies surprisingly reported an increase in RDW after 3–6 months of CPAP [ 43 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation